Energy Drinks: Effects on Blood Pressure and Heart Rate in Children and Teenagers. A Randomized Trial - Oberhoffer, Felix Sebastian; Li, Pengzhu; Jakob, André; Dalla-Pozza, Robert; Haas, Nikolaus Alexander; Mandilaras, Guido (Frontiers in Cardiovascular Medicine, 2022)
Background The consumption of Energy Drinks (ED) is very popular among children and teenagers. While potential cardiovascular side effects of these beverages are suggested, the acute impact of ED consumption on the pediatric cardiovascular system has not been systematically examined yet. The aim of this study was to investigate the acute effects of ED consumption on blood pressure and heart rate in healthy children and teenagers. Methods This study was a randomized, single-blind, placebo-controlled, crossover clinical trial. On two consecutive days, the study participants were asked to consume a weight-adjusted amount of an ED (3 mg caffeine per kg of body weight) or a placebo containing a similar amount of sugar but without conventional ED ingredients. Systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate were measured at the following time points: baseline as well as 30, 60, 120 and 240 min after beverage consumption. Results In total, 27 healthy children and adolescents (mean age 14.53 ± 2.40 years, 14 male) were included in the present study. Compared to placebo intake, mean SBP was demonstrated to be up to 5.23 mmHg (p < 0.0001) and mean DBP up to 3.29 mmHg (p < 0.001) increased after ED consumption. Prevalence of elevated blood pressure, stage 1 and stage 2 hypertension was higher after ED consumption. Heart rate tended to be lower after ED consumption. Conclusions The acute ED consumption is associated with a significantly increased SBP and DBP in healthy children and teenagers. Minors, particularly those with pre-existing health conditions, should be discouraged from drinking EDs. Clinical Trial Registration https://www.drks.de/drks_web/, identifier: DRKS00027580.